Kajian kapasitansi membran akibat variasi massa kitosan (Study of membrane capacitance due to mass variation of chitosan) - Monicha Esti; - Gusnedi; - Ratnawulan (PILLAR OF PHYSICS, 2013)
ABSTRACTMembrane is a layer that separates the two phases and organize mass transfer of the two phases were separated. Chitosan can be used as materials for membrane by dissolving chitosan powder in acetic acid 1 %. To obtain membranes that have good physical qualities, it is necessary to research on the physical properties of membranes. This type of research is experimental research with samples of chitosan membranes made of chitosan powder with chitosan mass variation is used as the membrane are 2 grams, 3 grams, 4 grams, 5 grams and 6 grams. Membrane capacitance values can be measured directly using the LCR meter 827. The highest value membrane capacitance is 6.10 ± 0.01 pF with a mass of chitosan used as membrane is 6 grams at  frequency 1 kHz. Membrane capacitance values have a tendency decreases with higher frequency. The highest value capacitance chitosan membrane after immersion in a solution of 20 mM KCl is 7.90 ± 0.01 with a mass of chitosan used as membrane is 4 grams at  frequency 1 kHz. Based on the research can be obtained an effect of mass of chitosan used as membrane due to capacitance chitosan membrane.Keywords : Membrane, Capacitance, Chitosan